Exposure to chronic early-life stress lastingly alters the adipose tissue, the leptin system and changes the vulnerability to western-style diet later in life in mice. (March 2017) - Yam, K.Y.; Naninck, E.F.G.; Abbink, M.R.; la Fleur, S.E.; Schipper, L.; van den Beukel, J.C.; Grefhorst, A.; Oosting, A.; van der Beek, E.M.; Lucassen, P.J.; Korosi, A.
Highlights: White adipose tissue (WAT), plasma leptin and leptin mRNA in WAT are lastingly reduced after chronic early-life stress (ES). Brown adipose tissue mass and browning of WAT is increased after ES exposure. Leptin receptor expression is upregulated in the choroid plexus and unaffected in the hippocampus in adulthood after ES. ES-induced cognitive impairments correlate with reduced adiposity in male mice only. Exposure to moderate western-style diet results in higher body fat accumulations in offspring with a history of ES. Abstract: Early-life stress (ES) increases the vulnerability to develop psychopathologies and cognitive decline in adulthood. Interestingly, this is often comorbid with metabolic disorders, such as obesity. However, it is unclear whether ES leads to lasting metabolic changes and to what extent this is associated with the ES-induced cognitive impairments. Here, we used an established chronic ES mouse model (from postnatal day (P) 2 to P9) to investigate the short- and long-term effects of ES exposure on parameters of the adipose tissue and the leptin system (i.e. circulating levels and gene expression of leptin and its receptor) in both sexes. Immediately following ES, the offspring exhibited reductions in white adipose tissue (WAT) mass, plasma leptin levels and in leptin mRNA expression in WAT. Furthermore, ES exposure led to increased brown adipose tissue and browning of WAT, which was evident by a drastic increase in uncoupling protein 1 mRNA expression in the inguinal WAT at P9. Notably, the ES-induced reductions in WAT mass, plasma leptin and leptin expression in WAT were sustained into adulthood and were accompanied by changes in body fat distribution, such as a higher ratio between mesenteric WAT and other WATs. Interestingly, while ES exposure increased leptin receptor mRNA expression in the choroid plexus, it was unaltered in the hippocampus. This suggests an adaptation to maintain central leptin homeostasis following ES exposure. In addition, chronic ES exposure resulted in the well-established cognitive impairment in object recognition performance during adulthood, which correlated positively with reductions in WAT mass observed in male, but not in female mice. Finally, to assess if ES leads to a different metabolic phenotype in a moderate obesogenic environment, we measured body fat accumulation of control and ES-exposed mice in response to a moderate western-style diet (WSD) that was provided during adulthood. ES-exposed mice subjected to WSD exhibit a higher increase in adiposity when compared to controls, suggesting that ES exposure might result in a higher vulnerability to develop obesity in a moderate obesogenic environment. To conclude, chronic ES exposure alters parameters of the adipose tissue, leads to central adaptations in leptin regulation and results in higher fat accumulations when exposed to a WSD challenge later in life. A better understanding of these metabolic effects induced by ES might open up new avenues for therapeutic (e.g. nutritional) interventions.